2012
DOI: 10.1080/15222055.2012.675999
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Plant and Animal Protein Sources as Partial or Total Replacement of Fish Meal in Diets for Nile Tilapia Fry and Juvenile Stages

Abstract: Two feeding trials were conducted in a closed system with Nile tilapia Oreochromis niloticus fry (mean weight, 0.10 g; experiment 1) and juveniles (mean weight, 2.84 g; experiment 2) to examine the effects of total replacement of fish meal (FM), with and without supplementation of DL-methionine (Met) and L-lysine (Lys), by plant protein sources. In experiment 1, fry were fed nine isoenergetic (available energy [AE] = 4.0 kcal/g of diet) and isoproteic (40% protein as fed basis) practical diets containing prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
17
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 33 publications
1
17
0
3
Order By: Relevance
“…Several studies evaluated alternative dietary protein sources for Nile tilapia (O. niloticus), such as plant proteins (El-Saidy and Gaber 2003;Fiogbé et al 2004;Azaza et al 2009;Kumar et al 2012) or animal proteins (El-Sayed 1998; Thompson et al 2012). However, not many studies focused on the use of seaweeds as a potential protein source for this important finfish species (Marinho et al 2013;Stadtlander et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies evaluated alternative dietary protein sources for Nile tilapia (O. niloticus), such as plant proteins (El-Saidy and Gaber 2003;Fiogbé et al 2004;Azaza et al 2009;Kumar et al 2012) or animal proteins (El-Sayed 1998; Thompson et al 2012). However, not many studies focused on the use of seaweeds as a potential protein source for this important finfish species (Marinho et al 2013;Stadtlander et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…, ; Thompson et al . ). Interestingly, a negative interaction between dietary amino acid and enzyme supplementation was clearly indicated ( P = 0.05–0.1) in almost all the whole‐body amino acid results, while the negative interaction between histidine and enzyme supplementation was highly significant ( P = 0.03).…”
Section: Discussionmentioning
confidence: 97%
“…Thompson et al . () found that tilapia juveniles fed a diet containing 200 g kg −1 FM had higher growth rates than fish fed a diet containing 100 g kg −1 FM. Therefore, the best growth in juvenile Nile tilapia occurs when fish are fed a diet containing 200 g kg −1 FM.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations